Visual analysis of leading Cancer sites using SPSS Software - Manikanta, V; Yethiraj, N.G (International Journal of Computer Sciences and Engineering, 2025)
Many diseases are arising depending upon the environment, culture, life style, etc. In many Diseases, Multiple types of cancer are increased in various region based on mouth, breast, cervix uteri, ovary, gall bladder, NHL, thyroid, Brain, Stomach, etc. Human of each organ is depending of the cell functionality. Each cell functionality is works our daily foods of sweet, sour, salty, etc. In our country many medical research centers are involved many research areas of Tuberculosis, Cancer, Diabetes, etc. Leading cancer sites data is one of the big tasks to region wise, gender wise, age wise, etc. The study of leading sites of cancer in various region wise, gender wise, age wise are easy to find the avoid the cancer to protect with any immediate solution. Visual analysis of data is easily exploring the details of Cancer leading site and analysis describes to how it is important to save our country for immediate treatment procedure